Diagnostic Value of Aortic Dissection Risk Score, Coagulation Function, and Laboratory Indexes in Acute Aortic Dissection - Song, Renjie; Xu, Nana; Luo, Lan; Zhang, Tianxi; Duan, Haizhen (BioMed research international, 2022)
Objective. This study was aimed at studying the diagnostic value of aortic dissection (AD) risk score, coagulation function, and laboratory indicators in acute aortic dissection (AAD). Methods. In this retrospective study, 57 patients with AAD and 57 with an acute coronary syndrome (ACS). During the same period, 50 healthy subjects were selected as the control group admitted to our institution which were assessed for eligibility and recruited. They were assigned to an AD group (AAD patients) and an ACS group (ACS patients). The AD risk scores, coagulation function indexes, and laboratory indexes of the two groups were compared. With digital subtraction angiography- (DSA-) based diagnosis result as the gold standard, the receiver operating characteristic (ROC) curve was used to analyze the diagnostic value of various indexes for AD, and the sensitivity, specificity, and optimal diagnostic value (Youden index) of the diagnostic indexes were calculated. Additionally, the overall blood clot formation strength (MA), clotting factor function (R), platelet function (MAp), and functional fibrinogen (MAf) levels were evaluated. Results. AAD risk, AD screening, early diagnosis of AAD, fibrinogen degradation products (FDP), fibrinogen (Fib), prothrombin time (PT), activated partial thromboplastin time (APTT), tenascin C (TN-C), D-dimer (D-D), and N-terminal B-type natriuretic peptide precursor (NT-proBNP) in the three groups were statistically different (P<0.05). Further pairwise comparisons showed that the AD patients got higher scores of AAD risk, AD screening, and early diagnosis of AAD versus ACS patients (P<0.05). AD was associated with lower levels of fibrinogen degradation products (FDP) and fibrinogen (Fib), shorter prothrombin time (PT), and activated partial thromboplastin time (APTT) versus ACS (P<0.05). AD also resulted in higher levels of tenascin C (TN-C), D-dimer (D-D), and N-terminal B-type natriuretic peptide precursor (NT-proBNP) versus ACS (P<0.05). The three risk scores, various laboratory indicators, and various coagulation function indicators were of high diagnostic values for the diagnosis of AAD (AUC>0.9, P<0.05). The sensitivity of the AD screening scale and TN-C expression level to the diagnosis of AAD was up to 100%, and the specificity of TN-C expression level was up to 98.25%. The influencing factors of AAD included Fib, FDP, PT, APTT, D-D, TN-C, and NT-proBNP. MA, MAf, and MAp displayed the same trend and reached the lowest point at T2. R was the opposite and reached the highest point at T2. At T4, a higher Map and a lower MAf were found than before surgery, and R and MA returned to preoperative levels. The positive detection rate of ACS by CT scan was positively correlated with the degree of stenosis (r=0.814, P<0.05). Conclusion. AD screening scale, TN-C, and FDP are of the highest diagnostic value in the risk score of AD, laboratory indicators, and coagulation function. It has implications for the diagnosis of ADD.